Nutritional Practice and Nitrogen Balance in Elite Japanese Swimmers during a Training Camp - Ami Mizugaki; Hiroyuki Kato; Haruka Suzuki; Hidefumi Kurihara; Futoshi Ogita (Sports, 2021)
The protein requirement in athletes increases as a result of exercise-induced changes in protein metabolism. In addition, the frequency, quantity, and quality (i.e., leucine content) of the protein intake modulates the protein metabolism. Thus, this study aimed to investigate whether nutritional practice (particularly, protein and amino acid intake at each eating occasion) meets the protein needs required to achieve zero nitrogen balance in elite swimmers during a training camp. Eight elite swimmers (age 21.9 ± 2.3 years, body weight 64.2 ± 7.1 kg, sex M:2 F:6) participated in a four-day study. The nitrogen balance was calculated from the dietary nitrogen intake and urinary nitrogen excretion. The amino acid intake was divided over six eating occasions. The nitrogen balance was found to be positive (6.7 ± 3.1 g N/day, p < 0.05) with protein intake of 2.96 ± 0.74 g/kg/day. The frequency and quantity of leucine and the protein intake were met within the recommended range established by the International Society of Sports Nutrition. Thus, a protein intake of 2.96 g/kg/day with a well-designated pattern (i.e., frequency throughout the day, as well as quantity and quality) of protein and amino acid intake may satisfy the increased need for protein in an elite swimmer.